Evaluation of The Implementation of The Independent Teaching Platform (PMM) Class VIII Social Studies Education Subjects at SMP Negeri Pontianak Selatan - Lingga, Metro; Widiastuti, Anik; Wulandari, Taat (STKIP Singkawang, 2025)
Evaluation of educational programs is very important to determine the success of program implementation and determine future improvements. Platform Merdeka Mengajar (PMM) provides opportunities for all teachers in Indonesia to continue learning and developing their competencies, whenever and wherever teachers are. This study aims to examine and analyze in depth the use of the Merdeka Mengajar Platform for the social studies learning process in grade VIII Junior High School in South Pontianak District. This type of research uses the Mixed Methods Explanatory Design research method. A combination of quantitative research with a qualitative approach. Data collection techniques through expert-validated questionnaires, observations, interviews and documentation studies. The results of the study found that the benefits of PMM felt by 85.71% of social studies teachers of SMP Negeri se Kecematan Pontianak Selatan were to obtain inspiration, reference and understanding in preparing for the social studies learning process. Teachers are motivated to continue learning, teaching and creating through the built environment at PMM. So, the results of this evaluation are expected to be the basis for further improvement and development in an effort to improve the effectiveness of the PMM program in the future.